Evaluasi Rate of Occurrence of Failure (ROCOF) and lifetime prediction at Integrated Drive Generator (IDG) air/oil cooler Boeing Aircraft 737-800 Garuda Indonesia at PT GMF Aero Asia - Arfandi Achmad; Fajar Khanif Rahmawati; Dwi Hartini (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2023)
The aviation industry in Indonesia demands an increase in the reliability and safety of aircraft according to CASR 43 through maintenance activities. One of the maintenance aircraft carried out is maintenance on the Integrated Drive Generator (IDG) Air/Oil Cooler Boeing 737-800 aircraft. IDG Air/Oil Cooler functions to transfer heat energy. Maintenance is carried out by repairing or replacing components depending on the level of damage. The method used for the IDG Air/Oil Cooler repair policy is a Power Law Process with a Non-Homogeneous Poisson Process. This study obtained an Increasing Failure Rate (IFR) with an average usage age or Mean Time To Failure (MTTF) of 8180.228022 Flight Hours. By using a reliability reference value of 70%, it can be recommended preventive maintenance measures with an interval of 5000 Flight Hours with a better reliability effect than without preventive maintenance applied.